THU0378 Impact of the adalimumab patient support program on clinical outcomes in ankylosing spondylitis: results from the companion study. (15th June 2017) - Bessette, L; Thorne, C; Millson, B; Charland, K; Donepudi, K; Gaetano, T; Remple, V; Latour, M; Laliberté, M-C
Abstract : Background: Adalimumab (ADL) is a TNF-alpha inhibitor indicated for various inflammatory autoimmune diseases including ankylosing spondylitis (AS). Patients receiving ADL in Canada are eligible to enroll in the AbbVie Care patient support program (PSP) which provides them with personalized services including ongoing care coach calls (CCC). In a previous study, rheumatology patients enrolled in Abbvie Care receiving CCC demonstrated significantly greater persistence and adherence to ADL than patients that did not receive CCC (no-CCC). Objectives: The objective of this study was to examine if ADL patients receiving CCC through the ADL PSP had an increased likelihood of achieving controlled disease state as determined by a Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) score <4 compared to those not receiving CCC. Methods: A longitudinal analysis using de-identified aggregate-level data collected through the AbbVie Care PSP was performed. Probabilistic matching was used to link patient-level records from the ADL PSP database to records from the QuintilesIMS longitudinal prescription transactions database (LRx). Patients were indexed on the date of their first ADL transaction between January 2010 and October 2015. The ADL PSP database included patient measurements of the BASDAI, a measure of disease activity. To be eligible, patients had to have a baseline BASDAI measurement between 90 days before and 30 days after their index date and have had a follow-up BASDAI measurement 6 to 18 months later. Only patients that were confirmed to be persistent on ADL as confirmed through the LRx records were included in the comparison. Controlled disease (BASDAI <4) at the time of the follow-up BASDAI assessment was compared in patients having received CCC and patients without CCC. Robust Poisson regression was used to estimate the adjusted relative risk (RR) of controlled disease. Analyses were adjusted for patient age group, sex, region, prior biologic use, days lapsed between BASDAI assessments, and baseline disease control status category. Results: A total of 249 AS patients met eligibility criteria and 123 (49%) of these had received CCC. Of the 249 patients, 184 (74%) had controlled disease (BASDAI <4) at the follow-up assessment, 98 (80%) in the CCC group and 86 (68%) in the no CCC group. In the multivariable regression analysis, there was a 23% increased likelihood of achieving controlled disease in the CCC group relative to the group without CCC (RR=1.23, 95% confidence interval: 1.06–1.42; p-value =0.0055). Conclusions: AS patients receiving tailored services through the ADL PSP in the form of care coach calls have an increased likelihood of achieving controlled disease within 6 to 18 months. These results may help refine interventions aiming at improving clinical outcomes in AS patients. Acknowledgements: Project management support for this study was provided by Jennifer Glass from QuintilesIMS. Analytical support was provided by Marc Duclos from QuintilesIMS. This support was funded by AbbVie. Disclosure of Interest: L. Bessette Grant/research support from: Abbvie, Amgen, BMS, Janssen, Roche, UCB, Pfizer, Merck, Celgene, Sanofi, Lilly, Novartis, Consultant for: AbbVie, Amgen, BMS, Janssen, Roche, UCB, Pfizer, Celgene, Lilly, Novartis, Speakers bureau: AbbVie, Amgen, BMS, Janssen, Roche, UCB, Pfizer, Merck, Celgene, Lilly, Novartis, C. Thorne Grant/research support from: Abbvie, Amgen, Celgene, CaREBiodam, Lilly, Novartis, Pfizer, Consultant for: AbbVie, Amgen, Celgene, Centocor, Genzyme, Hospira, Janssen, Lilly, Medexus/Medac, Merck, Novartis, Pfizer, Sanofi, Speakers bureau: Medexus/Medac, B. Millson Consultant for: AbbVie, Employee of: QuintilesIMS, K. Charland Consultant for: AbbVie, Employee of: QuintilesIMS, K. Donepudi Consultant for: AbbVie, Employee of: QuintilesIMS, T. Gaetano Shareholder of: AbbVie, Employee of: AbbVie, V. Remple Shareholder of: AbbVie, Employee of: AbbVie, M. Latour Shareholder of: AbbVie, Employee of: AbbVie, M.-C. Laliberté Shareholder of: AbbVie, Employee of: AbbVie